Insulin Resistance in the Offspring of Parents with Type 2 Diabetes - Wagenmakers, Anton J. M (Public Library of Science, 2005)
Wagenmakers discusses the paper by Petersen and colleagues on insulin resistance in young lean individuals and its association with reduced phosphate transport into muscle cells and impaired mitochondrial energy generation in muscle.